SEMINARY FORMATION: ADDRESSING CLERICALISM AND SEXUALITY - Schuth, Katarina (Asian Horizons, 2020)
During the past two decades, Church leaders throughout the world have grown increasingly concerned about the causes and context of clergy sexual abuse of minors. For many centuries, the Church issued no universal documents requiring seminaries to adapt formation programs in response to religious and cultural changes. The connection between sexual abuse and clericalism has surfaced only recently. A review of seminary practices indicates that administrators and faculty have made progress in amending some areas of formation, especially human formation, introduced in Pastores Dabo Vobis in 1992 by St Pope John Paul II. Even so, seminary leaders consider necessary many more improvements. The situation requires giving more attention to the development of affective maturity in seminarians in all areas of formation, especially by evaluating and correcting behaviours in pastoral settings that exhibit an attitude of clericalism. The Vatican’s 2016 Ratio Fundamentalis Institutionis Sacerdotalis affirms these directions.